Answer:
![\displaystyle f^(-1)(x)=(3+x)/(x-2)](https://img.qammunity.org/2021/formulas/mathematics/college/xgi975l5oacg80ekk23um2y2hissndywf0.png)
Explanation:
We have the function:
![\displaystyle f(x)=(2x+3)/(x-1)](https://img.qammunity.org/2021/formulas/mathematics/college/5b68zoqvdrtudmltlpq73lajy6knt2wx34.png)
Find the inverse of f(x). First, we call y=f(x):
![\displaystyle y=(2x+3)/(x-1)](https://img.qammunity.org/2021/formulas/mathematics/college/d66okv0gvkl3cj18f0utpiltce2xglh63t.png)
We have to solve for x. Multiply by x-1:
![y(x-1)=2x+3](https://img.qammunity.org/2021/formulas/mathematics/college/7han1il7jtu454rdvli83pr0bpjd9wlxr2.png)
Operate:
![yx-y=2x+3](https://img.qammunity.org/2021/formulas/mathematics/college/uzx8tokvgagwv80ecw4166apxb1jfsxs65.png)
Join all the x's to the left side and move the rest to the right side:
![yx-2x=3+y](https://img.qammunity.org/2021/formulas/mathematics/college/j6yc7b1wb259nataj9m4o0xg959fduxqoa.png)
Factor:
![x(y-2)=3+y](https://img.qammunity.org/2021/formulas/mathematics/college/6jsamprpym7udjn0sc7v5r5jro8uvyew7w.png)
Solve for x:
![\displaystyle x=(3+y)/(y-2)](https://img.qammunity.org/2021/formulas/mathematics/college/v3wdnyx9j0dava2ej2i5nhxx62he3le9zx.png)
Interchange the variables:
![\displaystyle y=(3+x)/(x-2)](https://img.qammunity.org/2021/formulas/mathematics/college/rkjnulvb1lxs0yhdhfkitdc894aauljbmu.png)
This is the inverse function:
![\boxed{\displaystyle f^(-1)(x)=(3+x)/(x-2)}](https://img.qammunity.org/2021/formulas/mathematics/college/tij1wdgztn4utkviazlwisfky0775n5tn2.png)